Compliance of adolescents with coeliac disease with a gluten free diet. Issue 8 (August 1991) - Mayer, M; Greco, L; Troncone, R; Auricchio, S; Marsh, M N
Abstract : A cohort of 123 patients with coeliac disease, diagnosed in the first three years of life and followed up for at least 10 years, was reevaluated during the teenage period in terms of compliance with the diet and clinical state. Mucosal structure and lymphocytes were assessed in small intestinal biopsy specimens obtained from 36 subjects, by computerised image analysis. Of these adolescents with coeliac disease, 65% were adhering to a strict gluten free diet, 11.4% were on a gluten free diet but with occasional gluten intake, and 23.6% were on a gluten containing diet. Clinical symptoms occurred more frequently in patients on a gluten containing diet, but not in patients on a semi-strict diet. Occasional intake of small amounts (0.06-2 g/day) of gluten did not produce increased concentrations of antigliadin antibodies but resulted in an appreciably increased crypt epithelial volume and expanded crypt intraepithelial lymphocyte population.